Influence of Public Participation on Enhancing Democratic Governance (International Journal of Scientific Research and Management (IJSRM), 2017)
Devolution framework in Kenya is anchored in article 174 of the Constitution which espouses the relationships where political, administrative and fiscal power is distributed to semi-autonomous territorial and sub-national units which seek to promote accountability, transparency, responsiveness and legitimacy in a state. For this to be achieved, the devolution framework borrows heavily on public participation framework. The purpose of this study was to establish the influence of public participation on enhancing democratic governance. The study adopted descriptive and correlation research design. All the forty-seven (47) counties in Kenya were targeted, with five officers per counties forming the sample frame. Regression models was used to examine the influence of the public participation on democratic governance in Kenya.The results revealed that there was a positive relationship between public participation and democratic governance. This finding implied that an improvement in public participation leads to an improvement in decentralized units. The study recommends for an inclusion of public input since it highly contributes to democratic governance and the feel of belonging of the people. Public participation is very critical for perception of fairness and justice